Social Welfare in the Soviet Union - Madison, Bernice Q. (Stanford, California: Stanford University Press, 1968)
This is a book about social welfare, and it is divided into two parts. Part one opens with a condensed analysis of major welfare developments during the ten centuries that preceded the October 1917 Revolution. An attempt is made to elucidate the basic philosophy that underlay social welfare in tsarist Russia, and to compare Russian welfare practices with those in various other European countries. Part 2 is an analysis of current Soviet social welfare practice and programs. It opens with an examination of social welfare organization and personnel.
Includes bibliographical references: p. [261]-291.
ne 5/06/2018
Loans
Keywords: Public welfare